EXPERIENCE IN DIAGNOSING RARE DIGESTIVE SYSTEM NEOPLASMS IN LABORATORY MICE - V. N. Manskikh; О. S. Gancharova (Сибирский онкологический журнал)
Three rare tumors occurring in laboratory mice, namely: myoepithelial carcinoma of the salivary gland, malignant neuroendocrine tumors (carcinoid) of the cecum and insular carcinoma of the pancreas have been described. Carcinoid tumor of the cecum was first diagnosed as a spontaneous neoplasm in mice without genetic modification. Analysis of diagnostic features of these neoplasms and their characteristics in comparison with the published cases has been presented.